The blue economy's retreat from equity: A decade under global negotiation - Louey, Philippa (Frontiers in Political Science, 2022)
Heralded as a key agenda for sustainable ocean development, the blue economy has risen to such prominence over the last decade that it is near impossible to engage in the fields of ocean governance or development without encountering it. The exact nature of the blue economy's sustainable ocean development promise, however, remains stubbornly unresolved, with different actors advancing varying, at times conflicting, visions of what sustainable ocean development should look like, how it is to be achieved, and who it is to serve. Tracing the various constructions of blue economy promises over the last decade, this paper contends that the blue economy has progressively retreated from its early commitment to equitable benefit sharing, shifting instead to a deepening preoccupation with economic growth. For small island developing states (SIDS) and coastal least developed countries (LDCs) who took a leading role in embedding equitable benefit sharing within the blue economy during its early popularization, such retreat raises pressing questions over the agenda's continued suitability in advancing desired (and often much needed) sustainable development outcomes. This paper's attempt to grapple with such questions offers a timely contribution to discussions on the blue recovery and ocean-led development avenues in the wake of COVID-19.